SantaKid - Patterson, James, 1947-; Garland, Michael, 1952- (New York : Little, Brown, 2004)
A businessman who is not very nice has bought the North Pole and Christmas, threatening to ruin that special day, and only Chrissie, Santa's daughter, seems to believe Christmas can be saved.
Accelerated Reader AR
Keywords: Santa Claus -- (Fictitious character) -- Fiction; Christmas -- Fiction; Magic -- Fiction; North Pole -- Fiction